Molecular mechanisms of diabetic kidney disease - Reidy, Kimberly (American Society for Clinical Investigation, 2014)
Diabetic kidney disease (DKD) is the leading cause of kidney failure worldwide and the single strongest predictor of mortality in patients with diabetes. DKD is a prototypical disease of gene and environmental interactions. Tight glucose control significantly decreases DKD incidence, indicating that hyperglycemia-induced metabolic alterations, including changes in energy utilization and mitochondrial dysfunction, play critical roles in disease initiation. Blood pressure control, especially with medications that inhibit the angiotensin system, is the only effective way to slow disease progression. While DKD is considered a microvascular complication of diabetes, growing evidence indicates that podocyte loss and epithelial dysfunction play important roles. Inflammation, cell hypertrophy, and dedifferentiation by the activation of classic pathways of regeneration further contribute to disease progression. Concerted clinical and basic research efforts will be needed to understand DKD pathogenesis and to identify novel drug targets.